ENGLISH LEARNING MOTIVATION OF NON-ENGLISH STUDENTS OF STMIK HANDAYANI MAKASSAR - Agus Rahmat; Muhammad Nasiruddin Sainu; Sukardi Weda (Leksema: Jurnal Bahasa dan Sastra, 2016)
This study describes (1) motivation in learning English, (2) influential factors in learning English, (3) influential motivation, and (4) ways to maintain and improve motivation to learn English.  This study used descriptive qualitative design. The subjects of the study were 20 EFL students sitting in semester I of STMIK Handayani Makassar in 2016.  Self report was used to collect data on motivation and interview was to explore in-depth features of motivation. The results show: (1) all 20 subjects were motivated in learning English; (2) factors affecting  motivation include internal factors, i.e. goal setting, expectancy, self confidence and  external factors, i.e. lecturer, classroom environment, activities, materials, the relevance, and feedback; (3) dominan influential motivation is instrumental motivation, and (4) to maintain and improve students’ motivation, English lecturers should use English in students’ proficiency, adaptable materials, comfortable classroom, communicative, creative,  patient, enthusiastic,  relax and friendly-smiling.